Sizing and selection of heat exchanger at defined saving-investment ratio - Agra, Ozden (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
In this study, a new model was developed to determine the size and the best type of heat exchanger for waste-heat-recovery systems at desired saving-investment ratio. The savings investment ratio is obtained as a function of the three dimensionless numbers: effectiveness, Number of Transfer Units and investment to saving potential ratio which is a function of technical and economical parameters. Rearranging the saving-investment ratio relation and multiplying investment to saving potential ratio and saving-investment ratio, a new dimensionless number which is called saving effectiveness was obtained as a function of effectiveness and Number of Transfer Units. This second dimensionless number was plotted on effectiveness and Number of Transfer Units charts which are available in the literature. Heat exchanger size at desired saving-investment ratio can be determined from the obtained charts or the correlation given as table. When desired saving-investment ratio is given saving effectiveness can be calculated than the effectiveness and Number of Transfer Units values cart be read from the charts or calculated for all types of heat exchangers. Afterwards, investment cost and saving can also be calculated easily. The best heat exchanger type is determined by comparing savings of different heat exchanger types for the same saving-investment ratio value. In addition, the model is explained using two case studies. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Effectiveness; NTU; Heat exchangers; Economical optimization; Saving-investment ratio; GENETIC ALGORITHMS; DESIGN; OPTIMIZATION; COST; Thermodynamics; Energy & Fuels; Engineering; Mechanics